(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Gravity explained by a new theory, ˜Superconducting String Theory (SST), inspired on initial string theories and completely opposite from actual fields based. Strengths are decomposed to make strings behave as one-dimensional with universe acting as a superconductor where resistance is near 0 and matter moves inside. Strong nuclear force, with an attraction of 10.000 Newtons is which makes space to curve, generating acceleration. More matter more acceleration. Electromagnetic moves in 8 decimals, gravity is moved to more than 30 decimals to work as a superconductor.